2013
DOI: 10.1177/1071100712472039
|View full text |Cite
|
Sign up to set email alerts
|

Subtalar Distraction Osteogenesis for Posttraumatic Arthritis Following Intra-Articular Calcaneal Fractures

Abstract: Level IV, retrospective case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…In case of absolute bone loss or extensive fragmentation and vascular impairment, distraction osteogenesis or vascularized bone transfers usually yield better results than does conventional cancellous bone grafting. 1,8,36 Fan and et al 8 reported good functional long-term outcomes in calcaneal reconstruction with distraction osteogenesis. Nonetheless, distraction osteogenesis is used only occasionally in Skin sensation in the plantar part of the foot cancellous small bone defects and has the problem of pin site infection.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In case of absolute bone loss or extensive fragmentation and vascular impairment, distraction osteogenesis or vascularized bone transfers usually yield better results than does conventional cancellous bone grafting. 1,8,36 Fan and et al 8 reported good functional long-term outcomes in calcaneal reconstruction with distraction osteogenesis. Nonetheless, distraction osteogenesis is used only occasionally in Skin sensation in the plantar part of the foot cancellous small bone defects and has the problem of pin site infection.…”
Section: Discussionmentioning
confidence: 98%
“…[2][3][4][5][6][7] Although distraction osteogenesis is seldom used to treat cancellous bone defects of the distal tibia or of the cuboid, navicular, and talar bones of the hind foot, it has served in the treatment of calcaneal defects. 8 Furthermore, an extensive soft tissue defect may preclude local flap options and thus require free soft-tissue flap reconstruction. 9,10 Vascularized bone transfers encourage revascularization and provide conditions conductive to bone healing.…”
mentioning
confidence: 99%
“…Inappropriately treated displaced calcaneal fracturealways leads to altered calcaneal morphology, including loss of height, heel widening, subfibular impingement, calcaneocuboid joint impingement, varus heel and subtalar joint incongruence, which further causes pain localized to the lateral, anterior, plantar or/and medial foot. Some studies have provided insight into the pain mechanics and reached a consensus on the diagnosis of localization: (i) lateral pain may be the result of peroneal tendon problems, subtalar arthrosis, calcaneocuboid arthrosis, symptomatic hardware, and/or sural nerve problems; (ii) pain localized to the anterior ankle is most commonly caused by anterior impingement of the talar neck on the distal tibia resulting from loss of the calcaneal height; (iii) plantar foot pain or heel pain may result from plantar exostosis or from injury to the heel pad; and (iv) medial pain may be the result of tarsal tunnel syndrome or flexor hallucis longus (FHL) tendon problems 14–17 . Thus, it is the disrupted anatomical relationship of the calcaneus that results in various symptoms following malunited calcaneal fractures, and the goal of surgical management is to restore physical anatomy to maximize the function and lifespan of the joint.…”
Section: Discussionmentioning
confidence: 99%
“…We read with great interest your recent publication of the article by Fan et al 2 In their retrospective study, they used external fixator to fix the subtalar joint following remove of the articular surface and subchondral bone of the posterior subtalar facet. And they concluded that this method was novel and effective for posttraumatic subtalar arthritis following intra-articular calcaneal fractures.…”
Section: Dear Editormentioning
confidence: 99%
“…First, although subtalar distraction osteogenesis with spanning external fixation could provide good clinical results, there are some disadvantages with the external fixation. 2 With external fixator spanning ankle and subtalar joints, the ankle joint space could be more easily widened rather than subtalar joint, thus leading to potential injury of the ankle joint. 3 Removal of the external fixator after bone fusion at an average of 4.9 months (range, 4-8 months) could result in the ankle stiffness.…”
Section: Dear Editormentioning
confidence: 99%